Pemertahanan Nilai-nilai Budaya Di Era Disrupsi 4.0 Melalui Video Pembelajaran Edukatif - Juli Rachmadhani (BAHAS, 2018)
ABSTRACTThe disruption era has affected all aspects of human life and cannot be separated from all human activities. Technological progress which is one of the effects of the disruption era has influenced the young generation of Indonesia to behave. The shift in cultural values such as the lack of politeness of the young generation is the real evidence that Indonesian is facing a moral crisis. The current phenomenon that is being faced by Indonesian is the language politeness of Indonesian generation that has begun to be broken. Only some of young people still maintain language politeness in daily life. In fact, language politeness is not innate, but there are certain factors that can affect someone's politeness. As Reiter in Murni (2018: 2) states that Language politeness is not innate but it is the result of socialization and construction of socio-cultural and history process of a nation. From his quote, we know that the main factor of language politeness of someone is because of socialization. The effect of technological progress has brought many effects to young generations’ behavior. They tend to follow the culture that is being trend setter which they see in their smartphones, and they forget the cultural values that their country has. This article deals with the preservation of cultural values in the disruption era 4.0 through educational learning videos. This educational learning video will show the cultural values of Indonesian behavior. This educational video is expected to be a medium of moral learning and regrow the cultural values that have been eroded by the times, since the cultural values that upholds the idea of language politeness is formed by a social setting. By this educational learning videos, the young generation of Indonesia will uphold the cultural values that are left behind in this disruption era.Keywords: cultural values, educational videos, disruption era.